Transcriptome Sequencing and Expression Analysis of Cadmium (Cd) Transport and Detoxification Related Genes in Cd-Accumulating Salix integra - Shi, Xiang; Sun, Haijing; Chen, Yitai; Pan, Hongwei; Wang, Shufeng (Frontiers in Plant Science, 2016)
Salix integra is a shrub willow native to northeastern China, Japan, Korea and Primorsky Krai in the far southeast of Russia, and has been identified as cadmium (Cd)-accumulating trees in recent years. Although many physiological studies have been conducted with these plants, little is known about the molecular basis underlying Cd response in this plant, and this is confirmed by the very few number of gene sequences (only 39 nucleotide sequences) available in public databases. Advances in genomics for Salix are promising for future improvement in identifcation of new candidate genes involved in metal tolerance and accumulation. Thus, high-throughput transcriptome sequencing is essential for generating enormous transcript sequences from S. integra, especially for the purpose of Cd toxicity-responsive genes discovery. Using Illumina paired-end sequencing, approximately 60.05 million high-quality reads were obtained. De novo assembly yielded 80,105 unigenes with an average length of 703 bp, A total of 50,221 (63%) unigenes were further functionally annotated by comparing their sequences to different proteins and functional domain databases. GO annotation reveals 1947 Cd responsive genes involving in Cd binding, transport and detoxification and cellular Cd homeostasis, and these genes were highly enriched in plant response to Cd ion and Cd ion transport. By searching against the PlantCyc database, 547 unigenes were assigned to 14 PlantCyc pathways related to Cd transport and cellular detoxification, and many of them are genes encoding heavy metal ATPases (HMAs), nature resistance-associated with microphage proteins (NRAMPs), ATP-binding cassette (ABC) transporters, etc. Comprehensive RT-qPCR analysis of these selected genes in different tissues of S. integra under the control and Cd treatment revealed metallothionein-like protein (MT2A and MT2B), Metal tolerance protein (MTP1), ABCB25, NRAMP5, and ZIP1 may be involved in the Cd transport and detoxification in leaves, while NRAMP2, ZIP8 and NRAMP5 may be related to Cd transport in roots. Our study will enrich the sequence information of S.integra in public database, and would provide some new understanding of the molecular mechanisms of heavy metal tolerance and detoxification in willows.